2013
DOI: 10.1158/1078-0432.ccr-12-3675
|View full text |Cite
|
Sign up to set email alerts
|

GKN1–miR-185–DNMT1 Axis Suppresses Gastric Carcinogenesis through Regulation of Epigenetic Alteration and Cell Cycle

Abstract: Purpose: Gastrokine 1 (GKN1) functions to protect the gastric antral mucosa and promotes healing by facilitating restoration and proliferation after injury. GKN1 is downregulated in Helicobacter pylori-infected gastric epithelial cells and loss of GKN1 expression is closely associated with gastric carcinogenesis, but underlying mechanisms of the tumor-suppressing effects of GKN1 remain largely unknown.Experimental Design: AGS, MKN1, MKN28 gastric cancer cells and HFE-145 immortalized nonneoplastic gastric muco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 24 publications
10
49
0
Order By: Relevance
“…We had previously found that GKN1 induces miR-185 expression in gastric epithelial cells and that miR-185 plays an inhibitory role in cell proliferation [11]. In the present study, we have shown that GKN1 induces miR-185 expression in AGS and MKN1 gastric cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…We had previously found that GKN1 induces miR-185 expression in gastric epithelial cells and that miR-185 plays an inhibitory role in cell proliferation [11]. In the present study, we have shown that GKN1 induces miR-185 expression in AGS and MKN1 gastric cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…4f). c-Myc inhibits miR-185 expression by binding to a promoter of miR-185 [11], and as such it is likely that c-Myc expression, induced by miR-34a silencing, leads to the inhibition of miR-185 expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations